Job Resources, Employee Engagement, and Innovative Work Behaviour of Bank Employees: Does Sex Matter? - Dei Mensah, Rebecca; Boateng, Richard kofi; Kwesi Papa Andoh, Raphael (Golden Ratio of Human Resource Management, 2025)
This study examined the relationships between job resources, employee engagement, and innovative work behavior among bank employees, taking into consideration gender differences. Data were gathered from 159 bank workers in the Cape Coast metropolis using a structured questionnaire, and data analysis was carried out using Structural Equation Modelling 4.9.8. A multigroup analysis was also done to assess how different gender roles affect the relationship between job resources, employee engagement, and the innovative work behavior of bank workers. The study found that job resources did not have a direct relationship with innovative work behavior but did so indirectly through employee engagement. Furthermore, the multigroup analysis revealed that when women have access to good job resources, they feel more engaged in their work, increasing their innovative behaviors compared to men. This study addresses a knowledge vacuum in the banking industry by examining the relationships between job resources, employee engagement, and innovative work behavior. It offers empirical evidence in a context that has yet to be extensively studied.